2015
DOI: 10.1111/1346-8138.12969
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of hypertrophic herpes simplex genitalis in HIV‐infected patient with topical imiquimod

Abstract: Hypertrophic herpes simplex genitalis is an atypical presentation of genital herpes described in the context of immunosuppression, particularly HIV-positive patients. This situation can become a diagnostic and therapeutic challenge. For this reason, alternative therapies are currently being discussed in the literature. We report a case of hypertrophic genital herpes in a HIV-positive patient who was successfully treated with topical 5% imiquimod after treatment failures with oral and i.v. antivirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The usual differential diagnosis for exophytic lesions in the anogenital area in the setting of HIV infection includes giant condyloma acuminatum, condyloma lata of secondary syphilis, mycobacterial lesions, squamous cell carcinoma, or lymphoma [6]. However, HSV infection can also present as hypertrophic or tumorous lesions [3, 5, 8–10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The usual differential diagnosis for exophytic lesions in the anogenital area in the setting of HIV infection includes giant condyloma acuminatum, condyloma lata of secondary syphilis, mycobacterial lesions, squamous cell carcinoma, or lymphoma [6]. However, HSV infection can also present as hypertrophic or tumorous lesions [3, 5, 8–10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, failure with thalidomide in the treatment of hypertrophic HSV lesions has also been reported [5]. Topical imiquimod has also been used successfully in the treatment of hypertrophic and pseudotumoral genital herpes simplex infection refractory to acyclovir and foscarnet [6, 12]. However, the response of herpes pseudotumors to imiquimod may require several months of treatment [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azacitidine treatment reduces the numbers of regulatory T (Treg), T-helper 1, and T-helper 2 cells in MDS patients. On the other hand, it is assumed that the imbalance in cytokine release secondary to the immune alterations could be responsible for the abnormal response to HSV-2 infection leading to hypertrophic HSV-2 lesions in HIV-infected patients [14]. In vitro studies have shown that azacitidine reduces the function of Treg cells and that the inhibitory effects of Treg cells on proliferation of T-effector cells and on cytokine secretion are subsequently decreased, resulting in an increased secretion of proinflammatory cytokines [13].…”
Section: Discussionmentioning
confidence: 99%
“…After a thorough review of literature there were other case reports also available relating to the use of imiquimod in the settings of acyclovir resistance or HIV co-infection (Deza, Martin-Ezquerra, Curto-Barredo, Villar García, & Pujol, 2015;Gilbert, Drehs, & Weinberg, 2001;Lascaux et al, 2012;Martinez, Molina, Scieux, Ribaud, & Morfin, 2006).…”
Section: Case Reportmentioning
confidence: 99%